The Use of Smartphones as Self Assessment for Teaching Skills - Nurani, Yuliani; Pratiwi, Niken; Kusumaningtyas, Nila (Indonesian Journal of Early Childhood Education Studies, 2018)
This research aimed to developof effective communication based teaching skills for early childhood education teacher which evolved according to Indonesian National Curriculum Framework used recently in Early Childhood Education Department, Faculty of Education, UniversitasNegeri Jakarta. This research is expected to facilitate early childhood teachers to assess their teaching ability. Smartphones can be used to document teaching skills while doing microteaching.This research is conducted on the students of PG PAUD study program Faculty of Education UniversitasNegeri Jakarta, which is following the course of Foundation of Curriculum and Curriculum: teaching practice, with the basic subject of teaching skill, theoretically and practically. Data were collected through the utilization of observation and document analysis and interview.The use of smartphones as self-assessment is appropriate to be used as one of the development of ECE teacher teaching skills model. 85% of student can directly and analyzed about their teaching skills by looking video in their smartphone. The result of this research that the use of smartphones is very efficient and practical, because almost all students have the gadget.